Implementasi Rancang Sistem Pencarian Kata Pada Kamus Bahasa Indonesia Menggunakan Metode Approximate String Matching Berbasis Web - Devin Febrian Kurnia; Hidayatullah Al Islami (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The dictionary is a reference that explains the meaning or meaning of a word. The use of dictionaries in the modern era is different from conventional dictionaries which have thick and very heavy weights. Finding words using conventional dictionaries also has constraints such as time consuming and small letters. The types of dictionaries also vary with the development of technology, one of which is an online dictionary. But the obstacle that must be experienced is not knowing for sure the word or finger slip that results in typo. This greatly affects the information obtained by the user, one of which is not getting the right words or not getting the words you are looking for. Thus we need a word search system in the Indonesian dictionary that is able to provide word suggestions typed by the user. One method of correcting word spelling is Approximate String Matching, this method applies a string search approach. The Levensthein Distance Algorithm is a part of the Approximate String Matching method. The Levensthein Distance algorithm has 3 kinds of string operations, namely deletion, addition and change.